2024
DOI: 10.1039/d4se00362d
|View full text |Cite
|
Sign up to set email alerts
|

Production of drop-in biodiesel blendstocks via competitive acid-catalyzed dehydration reactions using ethanol oligomerization products

Emmanuel Canales,
Samuel C. Hower,
Daniel Paul Li
et al.

Abstract: Ethanol can be converted into diesel fuel ethers using a three-step catalytic approach that involves ethanol oligomerization to larger alcohols, hydrogenolysis of the esters followed by dehydration of the C4...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Phung et al studied the conversion of ethyl acetate over HY zeolites and observed that the acetic acid formed undergoes decomposition reactions on the catalyst to produce methane, CO 2 , and coke precursors, leading to a decrease in ethyl acetate conversion with time on stream. In previous work on dehydration of alcohols, our group also observed increased coke formation in the presence of esters compared to control experiments without esters. , Therefore, approaches to minimize the ester content of the reactant mixture prior to dehydration are needed to prevent a loss of catalyst activity.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Phung et al studied the conversion of ethyl acetate over HY zeolites and observed that the acetic acid formed undergoes decomposition reactions on the catalyst to produce methane, CO 2 , and coke precursors, leading to a decrease in ethyl acetate conversion with time on stream. In previous work on dehydration of alcohols, our group also observed increased coke formation in the presence of esters compared to control experiments without esters. , Therefore, approaches to minimize the ester content of the reactant mixture prior to dehydration are needed to prevent a loss of catalyst activity.…”
Section: Introductionmentioning
confidence: 80%
“…We have previously studied ethanol conversion over a Cu catalyst supported on Mg–Al mixed oxides to produce a blend of alcohols, aldehydes, esters, ketones, ethers, and olefins. , We have then studied the dehydration of this mixture with an HY zeolite as shown in Scheme as reactions R1 and R2, where R1 produces diesel-range ethers . The mixture to be dehydrated contains esters that can hydrolyze over acid catalysts to produce carboxylic acids and alcohols (R3) or directly convert into carboxylic acids and alkenes (R4). , Carboxylic acids are known to adsorb strongly on the catalyst surface, causing catalyst deactivation .…”
Section: Introductionmentioning
confidence: 99%